Vaccination with viral vectors expressing NP, M1 and chimeric hemagglutinin induces broad protection against influenza virus challenge in mice. Issue 37 (3rd September 2019) - Asthagiri Arunkumar, Guha; McMahon, Meagan; Pavot, Vincent; Aramouni, Mario; Ioannou, Andriani; Lambe, Teresa; Gilbert, Sarah; Krammer, Florian
Abstract: Seasonal influenza virus infections cause significant morbidity and mortality every year. Annual influenza virus vaccines are effective but only when well matched with circulating strains. Therefore, there is an urgent need for better vaccines that induce broad protection against drifted seasonal and emerging pandemic influenza viruses. One approach to design such vaccines is based on targeting conserved regions of the influenza virus hemagglutinin. Sequential vaccination with chimeric hemagglutinin constructs can refocus antibody responses towards the conserved immunosubdominant stalk domain of the hemagglutinin, rather than the variable immunodominant head. A complementary approach for a universal influenza A virus vaccine is to induce T-cell responses to conserved internal influenza virus antigens. For this purpose, replication deficient recombinant viral vectors based on Chimpanzee Adenovirus Oxford 1 and Modified Vaccinia Ankara virus are used to express the viral nucleoprotein and the matrix protein 1. In this study, we combined these two strategies and evaluated the efficacy of viral vectors expressing both chimeric hemagglutinin and nucleoprotein plus matrix protein 1 in a mouse model against challenge with group 2 influenza viruses including H3N2, H7N9 and H10N8. We found that vectored vaccines expressing both sets of antigens provided enhanced protection against H3N2 virus challenge when compared to vaccination with viral vectors expressing only one set of antigens. Vaccine induced antibody responses against divergent group 2 hemagglutinins, nucleoprotein and matrix protein 1 as well as robust T-cell responses to the nucleoprotein and matrix protein 1 were detected. Of note, it was observed that while antibodies to the H3 stalk were already boosted to high levels after two vaccinations with chimeric hemagglutinins (cHAs), three exposures were required to induce strong reactivity across subtypes. Overall, these results show that a combinations of different universal influenza virus vaccine strategies can induce broad antibody and T-cell responses and can provide increased protection against influenza.